RESPON PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS BUNGA KOL (Brassica oleracea var. botrytis L.) TERHADAP PENGGUNAAN PUPUK MAJEMUK NPK DI DATARAN RENDAH - Taufan Yudha Prawoto; Sri Hartatik (UPT Penerbitan Universitas Jember, 2018)
The content of cauliflower is very beneficial for the human body, it encourages many people to consume these plants. But it isn’t matched by the amount of production, productivity and harvesting area of cauliflower plants whose development is fluctuating and tends to decrease, so that cultivation innovations are needed in terms of the varieties and fertilizers used. The purpose of this experiment was to determine the response and results of various types of NPK compound fertilizer in the lowland. The trial was conducted in Kalirejo Village, Dringu Subdistrict, Probolinggo. Manufacturing time in February until May 2018. The experiment used a 4 x 4 factorial Completely Randomized Design (CRD) model and repeated three times. The first factor is the Cauliflower varieties, namely PM 126 F1 (V1), Orient (V2), Diamond 40 (V3), and Holly (V4). The second factor is the dose of NPK compound fertilizer, namely 0 (P0), 3.72 (P1), 7.44 (P2) and 11.16 grams / plant (P3). The results of the experiment showed that the response between cauliflower varieties and NPK compound fertilizer had a significant effect on the parameters of weight of cauliflower with the best combination of Diamond 40 varieties with NPK 7.44 grams / plant compound fertilizer dosage (V3P2). Orient varieties provide the best response to growth and yield of cauliflower. The dosage of compound fertilizer NPK 7.44 grams / plant can increase the growth and yield of cauliflower